Fiqh Education at Mahad Aly Zawiyah Jakarta: A Solution for the Urban Dakwah Needs of Today - Badrah Uyuni; Mohammad Adnan; Rabiah Al Adawiyah; Fahmi Islam Jiwanto; Sirojuddin Sirojuddin (STAI Syaichona Moh. Cholil Bangkalan, 2024)
This study investigates the role of Mahad Aly Zawiyah Jakarta in providing a specialized Fiqh education that addresses the unique demands of urban dakwah. With urbanization increasingly shaping the lives of Muslims in city environments, traditional approaches to religious learning often struggle to meet the practical and ethical challenges faced by urban communities. As a result, many urban Muslims may develop a limited or superficial understanding of Islamic principles. Employing a qualitative case study approach, this research gathers data through interviews with educators and students, observations of classroom practices, and analysis of institutional documents to examine the curriculum, teaching methods, and impact of Zawiyah Jakarta’s Fiqh education program. Findings reveal that Zawiyah Jakarta effectively combines traditional Fiqh education with an awareness of modern urban issues, enriching urban dakwah efforts by addressing contemporary challenges. Notable features of Mahad Aly Zawiyah’s curriculum include contextualizing Fiqh teachings specific to urban settings, including ethical decision-making frameworks, and integrating contemporary societal issues, making the program highly relevant for urban Muslims. This study contributes valuable insights into Islamic education by presenting Zawiyah Jakarta’s program as a replicable model that other Islamic educational institutions can adapt. It offers a comprehensive framework for Fiqh education in urban contexts.